EXPERIMENTAL DESIGN TO ANALYZE THE EFFECT OF WRITING FORMAT ON STUDENT READING COMPREHENSION ON PAPER MEDIA USING COMPLETELY RANDOMIZED FACTORIAL DESIGN - Yuwana Adam, Rexy Satrya; Hadi, Yuswono (JEMIS (Journal of Engineering & Management in Industrial System), 2018)
Paper writing with the existing writing format causing excessive paper usage. Excessive paper usage could lead to environmental destruction. Therefore, it is necessary to find an alternative in the writing procedure by doing an experimental design based on student reading comprehensive. This study uses Completely Randomized Factorial Experimental Design. After analysis of variance and the multiple comparisons test done, it results a new writing format alternative that use less paper than the existing writing procedure. In other hand, it results greater student reading comprehensive than the existing writing procedure. With the results, the application of the alternative procedure can save the paper usage and make student easier to understand the paper.